Research review-sustaining participation in Massive Open Online Course (MOOC) - Jackson, Richard (Universiti Malaysia Sarawak (UNIMAS), 2018)
Massive Open Online Course (MOOC) is a tool to deliver education which can be enrolled by massive amount of students with massive amount of courses provided. However, the phenomenon of high dropout from MOOC with completion rate range from 6% to 11% made researcher interested to look at the reasons of dropping out from MOOC and the ways to sustain participation in MOOC from the existing studies that been made by other researchers. Existing studies were collected from three different databases (Google scholar, Jurn and National Association of Scholars) and analyzed using a cyclical process. The findings show that there were 10 themes (less experienced of using MOOC, lack of motivation, no penalty for dropping out, education level, weak course content, technology barrier, language barrier, absence of real-life partner, insufficient time and not interested) on the reasons of dropping out from MOOC and 7 themes (gamification, interaction, light workloads, course design, adaptive learning course, alignment of learning model and technological framework and motivation enhancement) on the ways of sustaining participation in MOOC. From the themes derived, there was a simple questionnaire done to look at the opinions of students in Universiti Malaysia Sarawak on the themes derived. The result of the survey show that not all reasons of dropping out from MOOC were agreeable by the respondents but all of the ways of sustaining participation in MOOC were agreeable by them. This study is expected to provide a better view and clearer understanding on the reasons of dropping out from MOOC and the ways of sustaining participation in MOOC.